The development of a pragmatic, clinically driven ultrasound curriculum in a UK medical school. (3rd June 2018) - Wakefield, Richard J.; Weerasinghe, Asoka; Tung, Patrick; Smith, Laura; Pickering, James; Msimanga, Tendekayi; Arora, Mohit; Flood, Karen; Gupta, Pawan; Bickerdike, Suzanne; McLaughlan, James; Uttley, Ashley; et al.
Abstract: Whether ultrasound (US) should be incorporated into a medical undergraduate curriculum remains a matter of debate within the medical education arena. There are clear potential benefits to its early introduction particularly with respect to the study of living anatomy and physiology in addition to the learning of clinical skills and procedures required for the graduate clinical practice. However, this needs to be balanced against what is perceived as an added value in addition to financial and time constraints which may potentially lead to the sacrifice of other aspects of the curriculum. Several medical schools have already reported their experiences of teaching US either as a standalone course or as a fully integrated vertical curriculum. This article describes and discusses the initial experience of a UK medical school that has taken the steps to develop its own pragmatic vertical US curriculum based on clinical endpoints with the intent of using US to enhance the learning experience of students and equipping them with the skills required for the safe practice as a junior doctor.